PERANCANGAN LAYANAN E-LIBRARY PADA SMP MANDIRI MALANG NENGAH TANGERANG - Syahriani Syahriani; Mulia Rahmayu; Deri Fardiansyah (LPPM UNIVERSITAS BINA INSAN, 2020)
The problem that is often faced by most Indonesian people is the lack of providing information about books quickly and accurately. The library at the Mandiri Malang Middle Nengah Tangerang is one of the libraries provided by the school to present information from the available books. However, the library facilities at SMP Mandiri Malang Nengah Tangerang are still relatively minimal and use conventional methods. This method is very ineffective because it takes time and money. Therefore, library services are needed using the programming language PHP and MySQL so that it can make it easier for students to access the library. In designing this e-library using the waterfall development method. The design of e-library services is expected to be more effective and efficient in finding a desired book. Keywords— Services, E-Library, Waterfall